2020
DOI: 10.3390/plants9060679
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species (ROS) and Nucleic Acid Modifications during Seed Dormancy

Abstract: The seed is the propagule of higher plants and allows its dissemination and the survival of the species. Seed dormancy prevents premature germination under favourable conditions. Dormant seeds are only able to germinate in a narrow range of conditions. During after-ripening (AR), a mechanism of dormancy release, seeds gradually lose dormancy through a period of dry storage. This review is mainly focused on how chemical modifications of mRNA and genomic DNA, such as oxidation and methylation, affect gene expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 113 publications
0
20
1
Order By: Relevance
“…Nucleic acid oxidation by ROS plays important biological roles, e.g. in release from dormancy in seeds, 142 but is also used as a marker of oxidative stress and 8-OHdG can be detected using antibody-based immunoassays, which have been exploited to observe increased DNA damage in Arabidopsis seeds lacking the base excision-repair enzyme AtOGG1. 143 Chromatographic (HPLC) methods have also be used to measure 8-OHdG in cryopreserved currant species exposed to temperatures of −20 and −196 °C.…”
Section: Measuring the Consequences Of Ros Oxidation: Redox Status Markersmentioning
confidence: 99%
“…Nucleic acid oxidation by ROS plays important biological roles, e.g. in release from dormancy in seeds, 142 but is also used as a marker of oxidative stress and 8-OHdG can be detected using antibody-based immunoassays, which have been exploited to observe increased DNA damage in Arabidopsis seeds lacking the base excision-repair enzyme AtOGG1. 143 Chromatographic (HPLC) methods have also be used to measure 8-OHdG in cryopreserved currant species exposed to temperatures of −20 and −196 °C.…”
Section: Measuring the Consequences Of Ros Oxidation: Redox Status Markersmentioning
confidence: 99%
“…Oxidative damage of nuclear DNA and mtDNA can be induced by the excessive accumulation of ROS in plant cells, which could also cause epigenetic variations in plants, such as DNA methylation/demethylation (Katsuya-Gaviria et al, 2020;Nagaraja et al, 2021) and histone modifications (Zheng et al, 2021) influencing plant development and growth. DNA damage caused by ROS could trigger the nuclear redox network and affect DNA metabolism through redox-dependent regulatory mechanisms comprising redox buffering and posttranslational modifications, such as the thiol-disulfide switch, glutathionylation, and S-nitrosation (Cimini et al, 2019).…”
Section: H 2 S and No Affect Mtdna Oxidative Damagementioning
confidence: 99%
“…Interestingly, it was recently demonstrated that AtPER1, a seed-specific peroxiredoxin, eliminates ROS to suppress ABA catabolism and GA biosynthesis, and thus improves the PD and make the seeds less sensitive to adverse environmental conditions [ 21 ]. In this Special Issue, Katsuya-Gaviria et al [ 22 ] review in detail the biological significance of nucleic acid oxidation caused by ROS during PD and germination. This update also refers to the state of the art regarding DNA and RNA methylation in seed biology.…”
Section: Ros and Nucleic Acid Modifications During Seed Dormancymentioning
confidence: 99%